1979
DOI: 10.1016/s0006-3495(79)85222-4
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium magnetic resonance study of the gel and liquid crystalline phases of dipalmitoyl phosphatidylcholine

Abstract: Deuterium magnetic resonance is applied to the study of the liquid crystalline and gel phases, and of the phase transition, of a multilamellar dispersion of chain perdeuterated (d62)-dipalmitoyl phosphatidylcholine/H2O. Analysis of the deuterium spectra in terms of the moments of the spectra allows one to make quantitative statements concerning the distribution of quadrupolar splittings even in complicated situations, e.g., when using perdeuterated sampled or when there are mixed phases. This analysis indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
251
2

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(282 citation statements)
references
References 37 publications
29
251
2
Order By: Relevance
“…However, several studies by infrared (6,(33)(34)(35), NMR (36,37), and Raman (38, 39) spectroscopy have shown that approximately a 2-7% fraction of gauche conformers is probably already present at temperatures below the transition, accounting for an average of 0.5-1.0 gauche bond per chain. The gauche rotamers are probably located mostly in kinks (gtg') or jogs (gttg') (34,40,41), which are not too disruptive of side-to-side order in the bilayer, or form end-gauche methyl groups (38).…”
Section: Orientation Measurements Of Phospholipid Bilayersmentioning
confidence: 99%
“…However, several studies by infrared (6,(33)(34)(35), NMR (36,37), and Raman (38, 39) spectroscopy have shown that approximately a 2-7% fraction of gauche conformers is probably already present at temperatures below the transition, accounting for an average of 0.5-1.0 gauche bond per chain. The gauche rotamers are probably located mostly in kinks (gtg') or jogs (gttg') (34,40,41), which are not too disruptive of side-to-side order in the bilayer, or form end-gauche methyl groups (38).…”
Section: Orientation Measurements Of Phospholipid Bilayersmentioning
confidence: 99%
“…2 H-nmr order profiles using selectively deuterated phospholipids have been established now for i,2-dipalmitoyl-.JM-glycero-3-phosphocholine (DPPC) , 1975, i,3-dipalmitoyl-jn-glycero-3-phosphocholine (Seelig & Seelig, 1977;Seelig & Waespe-Sarcevic, 1978) and i,2-dipalmitoyl-.ro-glycero-3-phosphoserine (DPPS) (Seelig & Browning, 1978;Browning & Seelig, 1980). In addition, egg-yolk lecithin with perdeuterated palmitic acyl chains intercalated physically , perdeuterated i,2-dipalmitoyl-sw-glycero-3-phosphocholine (Davis, 1979) and a glycolipid (Skarjune & Oldfield, 1979) have been studied. Though limited in number these order profiles comprise a fairly representative collection of different lipid classes, including saturated and unsaturated fatty acyl chains as well as different polar groups.…”
Section: (2) Order Profiles Of Model Membranes and Biological Membranesmentioning
confidence: 99%
“…c Brown, Seelig & Haberlen (1979). A Davis (1979 microviscosity) refers to membranes in general and is independent of the specific technique employed. This is also illustrated by fluorescence spectroscopy, where it has been realized only recently that the interpretation of fluorescence depolarization measurements exclusively in terms of microviscosity is incorrect, but that the fluorescence anisotropy is equally dependent on the ordering of the fluorescent probe in the membrane (Heyn, 1979;Jahnig, 1979).…”
Section: Phospholipid Dynamics and Membrane Fluiditymentioning
confidence: 99%
“…The average orientational order in the whole-lipid samples was quantified by determining the moments of the 'H-NMR spectra obtained from them (Davis, 1979). Arrhenius plots of the moments calculated from the spectra a11 increased between 30 and 0°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This two-pulse sequence results in a quadrupole spin echo at a time T after the second pulse that is due to a complete refocusing of the nuclear magnetization, provided that relaxation effects can be neglected. Since dead times for spectrometers are in the range of 10 to 20 ps and relaxation times for deuterated lipids range from 100 to 500 ps (Prosser and Davis, 1992), it is usually possible to select a value of T that is much greater than the recovery time of the spectrometer but much smaller than the relaxation time (Davis, 1979(Davis, , 1983.…”
Section: Nmr Measurementsmentioning
confidence: 99%